Pengaruh konsentrasi pati garut dan filtrat kunyit putih sebagai antimikroba terhadap karakteristik dan organoleptik edible film - Meditya Dwi Rizkyati; Sri Winarti (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Edible film is one of the biodegradable packaging that can be degraded naturally and is generally used to wrap food and is fit for consumption. Edible films are generally made from various types of starch, one of which is arrowroot starch and additional ingredients such as white turmeric filtrate which has antimicrobial activity to protect the packaged product from pathogenic bacteria and can extend the shelf life of the packaged product. White turmeric filtrate contains phenolic compounds and terpenoids as antimicrobial compounds. The purpose of this study was to determine the effect of arrowroot starch concentration and white turmeric filtrate on the characteristics and organoleptic properties of edible films. This study used a completely randomized design (CRD) factorial pattern with two factors. Factor I: arrowroot starch concentration (2%;4%;6%). and Factor II: white turmeric filtrate concentration (1%;4%;7%). The results of data analysis using 5% ANOVA and 5% DMRT follow-up test. The data obtained from the analysis showed that the best treatment was edible film from arrowroot starch 4% (w/v) and white turmeric filtrate 7% (v/v) having edible film characteristics with a water content of 13.109%; thickness 0.115 mm; tensile strength 7.69 Mpa; elongation 1.96%; water vapor transmission rate 0.29 g/m2.hour; inhibition against E.coli bacteria by 16.5 mm; inhibition against S. aureus bacteria 6.5 mm; texture 4 (slightly broken); color 4.75 (yellow); and aroma 3.9 (scented with strong turmeric).